2014
DOI: 10.1016/j.cbpa.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessing stimulus and subject influences on auditory evoked potentials and their relation to peripheral physiology in green treefrogs (Hyla cinerea)

Abstract: Anurans (frogs and toads) are important models for comparative studies of communication, auditory physiology, and neuroethology, but to date, most of our knowledge comes from in-depth studies of a relatively small number of model species. Using the well-studied green treefrog (Hyla cinerea), this study sought to develop and evaluate the use of auditory evoked potentials (AEPs) as a minimally invasive tool for investigating auditory sensitivity in a larger diversity of anuran species. The goals of the study wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 119 publications
(203 reference statements)
2
17
0
Order By: Relevance
“…Specifically, we measured the auditory brainstem response, a type of AEP which is generated by the auditory periphery, occurs in response to the onset of sound and is seen within 10 ms of the arrival of the stimulus at the ear. The green treefrog response consists of two peaks, P1 and P2 [21]. We found that P1 was only consistently measurable from frequencies of 0.8 to 1.6 kHz (figure 2).…”
Section: (B) General Experimental Proceduresmentioning
confidence: 87%
See 4 more Smart Citations
“…Specifically, we measured the auditory brainstem response, a type of AEP which is generated by the auditory periphery, occurs in response to the onset of sound and is seen within 10 ms of the arrival of the stimulus at the ear. The green treefrog response consists of two peaks, P1 and P2 [21]. We found that P1 was only consistently measurable from frequencies of 0.8 to 1.6 kHz (figure 2).…”
Section: (B) General Experimental Proceduresmentioning
confidence: 87%
“…The threshold is then estimated as lying halfway between this stimulus intensity and the next lowest intensity (in our case, 2.5 dB below the stimulus intensity of the last detectable response). This method consistently produces evoked potential thresholds that provide the greatest agreement with thresholds estimated with single unit or behavioural estimates [17,21,29].…”
Section: (B) General Experimental Proceduresmentioning
confidence: 91%
See 3 more Smart Citations